2016
DOI: 10.1177/0907568215625758
|View full text |Cite
|
Sign up to set email alerts
|

A “snapshot” of physical activity and food habits among private school children in India

Abstract: Concerns about increasing obesity in poorer parts of the world, including India, have often been premised in terms of global shifts in activity levels and caloric consumption. Lifestyle changes have been documented in large cities, but we do not know whether these changes are reaching young people in less urban locations. This study used photo journals to explore children’s perceptions of their food and activity habits in a remote Indian city. Children expressed interest in active pastimes, learning, and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The reproducibility and validity of the NT-FFQ were evaluated among 200 adolescents aged 14–18 years. These 200 adolescents were interviewed as a part of the follow-up of a longitudinal study of 407 adolescents who participated in the 2012 Home Environment and Adolescent Body Weight study in Vijayapura ( 29 ) . In the 2012 baseline study, a representative stratified random school-based sample of 407 adolescents was drawn from three public and three private schools in Vijayapura.…”
Section: Methodsmentioning
confidence: 99%
“…The reproducibility and validity of the NT-FFQ were evaluated among 200 adolescents aged 14–18 years. These 200 adolescents were interviewed as a part of the follow-up of a longitudinal study of 407 adolescents who participated in the 2012 Home Environment and Adolescent Body Weight study in Vijayapura ( 29 ) . In the 2012 baseline study, a representative stratified random school-based sample of 407 adolescents was drawn from three public and three private schools in Vijayapura.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in Karnataka used photo journals to understand this and found children to be interested in active pastimes as well. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Vijayapura, specifically, families whose children attend government schools earned a median monthly income of INR 5,001-10,000 (approximately USD 79-159) (Staab et al 2016). For families whose children attend private schools, the median monthly income was INR 10,000-20,000 (USD 158-317) (Staab et al 2016). This reflects the substantial fees required to attend private schools; government schools are free or nearly free.…”
Section: Ethnographic Background and The Changing Food Environment Inmentioning
confidence: 98%
“…Among Indian adolescents, government or private school attendance is generally a good indicator of socioeconomic status (Reddy and Gibbons 1999). In Vijayapura, specifically, families whose children attend government schools earned a median monthly income of INR 5,001-10,000 (approximately USD 79-159) (Staab et al 2016). For families whose children attend private schools, the median monthly income was INR 10,000-20,000 (USD 158-317) (Staab et al 2016).…”
Section: Ethnographic Background and The Changing Food Environment Inmentioning
confidence: 99%